POLA LALU LINTAS INFORMASI KOMUNITAS PENGUSAHA KAMPUS MEMBENTUK GERAKAN PENGUSAHA MUDA BEDA MENDUNIA MELALUI WHATSAPP MESSENGER - Santi Rahmawati (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2018)
This research aim to know an information traffic pattern in community of Campus Enterpreneur which using Whatsapp messenger. This research method is case study and do in depth interview and observation. Aplied concepts in four pattern, base on Borderwijk and Van Kaam concept, these are allocution, conversation, consultation and registration. The result of information traffic pattern is in the beginning of recruitment, controlled in-formation to the coordinating center of the Chairman (alokusi stage). Once incorporated in social networks, the conversation takes place between one member and the other (the conversation phase), about the mission vision, goals, organizational structure, work pro-gram, and existence in the community. The Chairman’s directive ensures that every re-gional activity can work (consultation phase). And the Chairman receives and controls information from the members of the region regarding the agenda to be held (registration stage).